Model Matematika Penyebaran Penyakit Scabies pada Populasi Hewan dan Manusia - Yani Sriyanti; Defri Ahmad (Journal of Mathematics UNP, 2020)
Abstract — Scabies is a contagious skin disease caused by an infestation of the Sarcoptes Scabie mite which can spread quickly. This disease is spread in tropical areas where the level of hygiene, sanitation, and socio-economy is low and attacks all groups regardless of sex and age. The purpose of this research is to form a mathematical model, then the model is analyzed and interpreted. Based on the asumi and parameter values, a mathematical model of the spread of scabies in animal and human populations can be formed. The model that has been formed will then be analyzed using simulation. From the analysis obtained two points of equilibrium, which disease free and disease endemic. The simulation results show that scabies disease will continue to exist in the population because the equilibrium point at the endemic disease is unstable.Keywords— endemic, mathematical model, scabies, basic reproduction number.